Monitoring and Automation System for Bird Feeding and Drinking Based on Internet of Things Using ESP32 - Allieffa Salsabilla Pradisthi; Joko Aryanto (Advance Sustainable Science Engineering and Technology, 2023)
Birds are vertebrate animals characterized by feathers and wings. Their melodious sounds and colorful plumage make them a popular choice for bird breeders, which presents a promising business opportunity. Manual feeding and drinking requires farmers to feed and drink every day, which often results in delayed feeding and drinking or inconsistent dosing, causing birds to become susceptible to disease and death. Therefore, this study is intended to create an automated system for monitoring feed and drink at predetermined times utilizing the Internet of Things (IoT) concept. The system's schedule can be remotely accessed and monitored through a website, and it operates in real-time without requiring manual intervention. This allows farmers to monitor and provide birds with food and water even from a distance. The Internet of Things (IoT) system utilized in this research employs an ESP32 microcontroller as the primary controller, which connects to a Wi-Fi network. It features a servo motor designed to refill bird feeders and drinkers. Further, a mini pump is used to replenish water in the drinker based on the owner's predetermined schedule set via the application. The research concludes that the tool functions based on the input time on the website. The system sends notifications to the breeder's smartphone regarding successful feeding and drinking, with an error rate of less than 20% in system testing and over 80% accuracy in system functioning. The outcome is in the form of a tool dispensing feed and drink daily, in accordance with the breeder's specified hours